1.4 GHz on the Fundamental Plane of black hole activity. Issue 2 (22nd March 2018) - Saikia, Payaswini; Körding, Elmar; Dibi, Salome
Abstract: The Fundamental Plane (FP) of black hole activity is an empirical relationship between the O iii /X-ray luminosity depicting the accretion power, the radio luminosity as a probe of the instantaneous jet power and the mass of the black hole. For the first time, we use the 1.4 GHz FIRST radio luminosities on the optical FP, to investigate whether or not Faint Images of the Radio Sky at Twenty-Centimetres (FIRST) fluxes can trace nuclear activity. We use an SDSS-FIRST cross-correlated sample of 10 149 active galaxies and analyse their positioning on the optical FP. We focus on various reasons that can cause the discrepancy between the observed FIRST radio fluxes and the theoretically expected core radio fluxes, and show that FIRST fluxes are heavily contaminated by non-nuclear, extended components and other environmental factors. We show that the subsample of 'compact sources', which should have negligible lobe contribution, statistically follow the FP when corrected for relativistic beaming, while all the other sources lie above the plane. The sample of low-ionization nuclear emission-line regions (LINERs), which should have negligible lobe and beaming contribution, also follow the FP. A combined fit of the low-luminosity AGN and the X-ray binaries, with the LINERs, results in the relation log L R = 0.77 log L_O III + 0.69 log M . Assuming that the original FP relation is correct, we conclude that 1.4 GHz FIRST fluxes do not trace the pure 'core' jet and instantaneous nuclear activity in the AGN, and one needs to be careful while using it on the FP of black hole activity.